THE EFFECT OF GINGER RHIZOME JUICE ON ACUTE TOXICITY OF PROPANOLOL AND QUINIDINE IN MICE - Purwantiningsih .; Lukman Hakim (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The rhizome of ginger (Zingiber officinale, Rosc.) has been consumed by most people, as food ingredient or a traditional drug. In the previous research there was evidence that the ginger juice influenced the pharmacokinetics of propranolol (representative of drugs with high extraction ratio) and of sulfamezathine (as a model of sulfonamide drugs). The aim of this research is to study the effect of juice of ginger on the acute toxicity of propranolol and quinidine (a drug with a narrow therapeutic range). To achieve the aim of this study, mice were divided randomly into two groups, propranolol and quinidine. The each group was divided subsequently into controlled and pretreated groups. Mice in the controlled groups were given propranolol (I: 69 mg/kg BW; II; 82,80 mg/kg BW; III: 99,36 mg/kg BW; IV: 119,23 mg/kg BW) or quinidine (I: 265 mg/kg BW; II; 344,50 mg/kg BW; III: 447,85 mg/kg BW; IV: 582,25 mg/kg BW) through intraperitoneal injection, and those in pretreated group were pretreated with the ginger juice orally (5,6 ml/kg BW) an hour prior administration of propranolol or quinidine. The observations of the effect were done during the first three hours. The mice were killed and the vital organs were taken for histopathologic examination. The values of LD-50 were computed by Miller-Tainter Method (propranolol; LD-50controlled = 89,98 mg/kg BB dan LD-50treated = 87,51 mg/kg BB] [quinidine; LD-50controlled = 418,48 mg/kg BB dan LD-50 treated =331,93 mg/kg BB]. The results of this research showed that the ginger juice influences the acute toxicity of quinidine but the acute toxicity of propranolol.Key words: ginger rhizome, acute toxicity, mice, quinide, propanolol